Adaptation of banks to sustainability requirements and impact on their financial performance - Mariana Bunea; Camelia-Daniela Hategan; Rodica Gabriela Blidisel; Adrian Doru Bigioi (Amfiteatru Economic, 2025)
At the banking system level, the implementation of sustainability requirements is an important goal in order to ensure long-term financial performance. Transparency of information included in banks' sustainability reports can be assessed through methodologies based on environmental impact criteria, governance, and social aspects (ESG). A high score on the impact criteria can bring benefits to the level of banks, but at the same time, the adoption of sustainability policies can increase operational costs. In this context, the objective of this research is to identify the correlation between a series of indicators that measure the performance of ESG and the financial performance of banks. The research is based on the econometric analysis applied to a sample of 76 banks in Europe for the period 2020-2023. Information was collected from the LSEG Refinitiv Eikon database, using financial indicators and ESG scores reported by banks, thus ensuring a relevant benchmarking analysis. The results obtained indicate a significant relationship between the financial performance of European banks and the factors of ESG, highlighting a negative correlation between the return on assets (ROA) and the governance score (G), as well as a positive influence of the ESG score on the return on equity (ROE). This research highlights how ESG factors influence the financial performance of European banks and their climate risk management strategies. It provides essential information for policymakers, investors, and regulators looking to integrate sustainability into banking practices.
Keywords: G21; L25; M40; 330; performance; banks; sustainability; ESG scores; reporting